A kaolin-based carbon dioxide adsorbent and a method for preparing the same by acid treatment

Through acid treatment and thermal activation treatment, the specific surface area and end surface exposure of kaolin are improved, and efficient kaolin-based carbon dioxide adsorbent is prepared, which solves the problems of structural damage and high cost in the prior art, and achieves efficient CO2 adsorption Performance improvement.

CN118698491BActive Publication Date: 2025-01-17CHINA-AFRICA KAOLIN MAOMING NEW MATERIALS CO LTD +1
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202410819724.2
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-06-24
Publication Date
2025-01-17
Estimated Expiration
2044-06-24

AI Technical Summary

Technical Problem

The prior art often destroys the structure of clay minerals when developing high-efficiency carbon dioxide adsorbents, resulting in a lengthy and high cost of preparation, and failing to fully utilize the natural adsorption properties of clay minerals.

Method used

The kaolin was treated by acid treatment to improve its specific surface area and end surface exposure, and a kaolin-based carbon dioxide adsorbent that does not destroy the structure was prepared. By regulating the relative texture coefficient and thermal activation treatment, its CO2 adsorption performance was enhanced.

Benefits of technology

The carbon dioxide adsorption performance of kaolin has been significantly improved, and the adsorption performance of natural kaolin has been increased by 1-3 times, and the process is simple and the cost is low.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN118698491B_ABST
    Figure CN118698491B_ABST
Patent Text Reader

Abstract

The present invention discloses a kaolin-based carbon dioxide adsorbent and a method for preparing the same by acid treatment. The present invention relates to the technical field of carbon dioxide adsorbents. The method comprises the following steps: reacting kaolin with a purity of not less than 85% with hydrochloric acid at a concentration of 1-5M in a water bath with stirring, centrifuging, washing with ionized water until the pH is neutral, drying, cooling, and grinding to obtain a sample, namely a kaolin-based carbon dioxide adsorbent, wherein the specific surface area of ​​the kaolin-based carbon dioxide adsorbent is greater than 12 m 2 / g. The present invention does not destroy the structure of kaolin and gives full play to the inherent characteristics of clay minerals, and improves the CO2 adsorption performance of kaolin through a simple process. The prepared kaolin-based carbon dioxide adsorbent has a carbon dioxide adsorption performance that is 1-3 times higher than that of natural kaolin.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of carbon dioxide adsorbents, and in particular to a kaolin-based carbon dioxide adsorbent and a method for preparing the same by acid treatment. Background Art

[0002] Carbon dioxide (CO2) is the main greenhouse gas, and the increase in CO2 concentration in the atmosphere can cause environmental problems such as global warming and ocean acidification. Global warming caused by greenhouse gases such as CO2 is one of the most challenging environmental problems facing today. Carbon capture and storage (CCS) technology is an effective measure to reduce CO2 emissions. In CCS, CO2 is captured from point sources such as refineries, cement plants or fossil fuel power plants and then injected into underground geological formations or further used for other purposes such as food processing (after purification) and enhanced oil recovery in the oil industry. However, the application of these methods is expensive and requires high energy. The capture and storage of CO2 using adsorbents has been proposed as a viable alternative to conventional CCS technology to reduce the energy required and achieve a more efficient process. Many efforts have focused on the development of adsorbents with CO2 selectivity and high adsorption capacity. Among them, clay minerals show promising behavior for CO2 capture processes in terms of catalysis and adsorption. Other advantages include the high stability and availability of clay minerals. Kaolin, as the main clay mineral, is a dioctahedral 1:1 layered silicate with the characteristics of large specific surface area and high porosity. It is a natural adsorbent for geological storage of CO2.

[0003] At present, kaolin resources are abundant, low in cost, and have a high specific surface area, abundant pores, high mechanical properties and chemical stability. It is often used as an excellent amino-functionalized solid adsorbent matrix material. By modifying it and applying it to the preparation of CO2 solid adsorbents, the CO2 adsorption performance can be improved.

[0004] Using kaolinite as raw material, a mesoporous silica carrier (KNH) was prepared by calcination-alkali activation-acid etching method, and then KNH was modified with pentaethylenehexamine (PEHA) to prepare a mesoporous composite material (KNH-PEHA). The adsorption temperature was 25°C, and the CO2 adsorption capacity of KNH was 147.39 cm 3 / g, while the CO2 adsorption capacity of KNH (KNH-P-30) with a PEHA mass fraction of 30% at equilibrium reached 389 cm 3 / g. (Chen Xinyi, Cheng Hongfei, Zhao Bingxin, Hu Mianshu, Jia Xiaohui. Carbon dioxide adsorption properties of kaolinite-based mesoporous composites[J]. Journal of Synthetic Crystals, 2021, 50(09): 1756-1764.)

[0005] Ethanolamine and N,N-dimethylethanolamine can effectively modify halloysite. Although the pore area, pore volume and pore diameter of the modified halloysite are reduced, the pore area distribution and pore volume distribution are increased. At the same time, the adsorption performance of CO2 is significantly improved. (Zhao Weijun, Zhang Huali, Yan Chunjie, Pan Zhiquan. Adsorption behavior of halloysite modified by ethanolamine and N,N-dimethylethanolamine for CO2[J]. Journal of Wuhan University of Technology, 2017, 39(05): 420-426.)

[0006] The above studies all use clay minerals as carriers to load high-performance alkaline substances that adsorb CO2 to form composite materials, which mostly destroy the original structure of clay minerals. Such preparation processes are lengthy and expensive. The advantages of the clay minerals' own structure are not utilized, and the advantages of clay minerals as natural adsorbents for geological storage of CO2 are not fully utilized. Summary of the invention

[0007] The purpose of the present invention is to address the above-mentioned deficiencies of the prior art and provide a kaolin-based carbon dioxide adsorbent and a method for preparing the same by acid treatment. The present invention does not destroy the kaolin structure, fully utilizes the inherent characteristics of the clay mineral, and improves the CO2 adsorption performance of kaolin through a simple process.

[0008] The present invention discloses a method for preparing a kaolin-based carbon dioxide adsorbent by acid treatment, wherein kaolin with a purity of not less than 85% is stirred in a water bath with hydrochloric acid having a concentration of 1-5M, and then centrifuged, washed with ionized water until the pH value is neutral, dried, cooled, and ground to obtain a sample, namely, a kaolin-based carbon dioxide adsorbent, wherein the specific surface area of ​​the kaolin-based carbon dioxide adsorbent is greater than 12m 2 / g.

[0009] Furthermore, the purity of the kaolin is 85-96%, the reaction temperature under water bath stirring is 50-90°C, the stirring speed is 100-300r / min, and the reaction time is 6-12h; the sum of the relative texture coefficients (RTCs) of the main end faces (020), (-110), (-1-11), (-201), (-131) and (-202) of the kaolin-based carbon dioxide adsorbent is >55.

[0010] Furthermore, the purity of the kaolin is 85-96%, and the reaction temperature under water bath stirring is 50°C.

[0011] Furthermore, the purity of the kaolin is 96-99%, the reaction temperature is 90°C with stirring in a water bath, the stirring speed is 100-300 r / min, the reaction time is 6-12h, and the specific surface area is >20m 2 / g.

[0012] Furthermore, the purity of the kaolin is 96-99%, and the reaction temperature under water bath stirring is 50-90°C.

[0013] Furthermore, the ground sample was subjected to thermal activation treatment and then cooled to room temperature, and then taken out to obtain a kaolin-based carbon dioxide adsorbent.

[0014] Further, the thermal activation treatment was carried out in a muffle furnace with a temperature increase of 5-10°C / min and a temperature maintenance of 100-400°C for 60 min.

[0015] Furthermore, the sum of the relative texture coefficients (RTCs) of the end surfaces (020), (-110), (-1-11), (-201), (-131) and (-202) of the kaolin-based carbon dioxide adsorbent is greater than 51.

[0016] Further, drying is carried out in an oven at 60-80°C for 6-12 hours.

[0017] A kaolin-based carbon dioxide adsorbent prepared by the above-mentioned method for preparing a kaolin-based carbon dioxide adsorbent by acid treatment.

[0018] The present invention does not destroy the structure of kaolin, fully utilizes the inherent characteristics of clay minerals, and improves the CO2 adsorption performance of kaolin through a simple process.

[0019] The present invention clearly defines specific surface area and end face exposure as the basis for determining the carbon dioxide adsorption performance of kaolin, thereby regulating kaolin to prepare carbon dioxide adsorption materials. The larger the specific surface area of ​​kaolin, the more physical adsorption of carbon dioxide by kaolin. The end face exposure of kaolin represents more -OH that can chemically adsorb carbon dioxide -OH+CO2→-HCO3. DFT calculations show that carbon dioxide produces strong hydrogen bonds with the end face, thereby increasing the amount of carbon dioxide adsorption.

[0020] The present invention uses acid treatment to treat low-purity 85-96% kaolin to mainly increase the exposure degree of the main end faces so that the sum of the relative texture coefficients (RTCs) of the main end faces (020), (-110), (-1-11), (-201), (-131) and (-202) is greater than 55, and the specific surface area of ​​the kaolin is greater than 12m 2 / g, and does not destroy the structure of kaolin.

[0021] Acid treatment of high purity 96-99% kaolin to increase specific surface area, specific surface area>20m 2 / g, 96-99% kaolin was treated with acid and then heat activated, so that the sum of the relative texture coefficients (RTCs) of the main end faces (020), (-110), (-1-11), (-201), (-131) and (-202) was greater than 51, and the structure of the kaolin was not destroyed.

[0022] The acid treatment of low-purity kaolin (the sum of the relative texture coefficients (RTCs) of the main end faces (020), (-110), (-1-11), (-201), (-131) and (-202) is low) is mainly used to increase the exposure of the end faces. The low-purity kaolin with a small intrinsic end face texture coefficient is treated with low-temperature concentrated acid to improve the CO2 adsorption performance, mainly because the end face exposure is increased, thereby increasing the presence of -OH.

[0023] High-purity kaolin (the sum of the relative texture coefficients (RTCs) of the main end faces (020), (-110), (-1-11), (-201), (-131) and (-202) is high) is treated with acid or acid and heat activation to mainly increase the specific surface area and the degree of end face exposure. High-purity kaolin with large end face texture coefficient is treated with high temperature and high concentration acid and then heat activated, which first increases the specific surface area and then increases the degree of end face exposure to improve CO2 performance.

[0024] The kaolin-based carbon dioxide adsorbent prepared by treating the kaolin with the method of the present invention has carbon dioxide adsorption performance improved by 1 to 3 times compared with that of natural kaolin. BRIEF DESCRIPTION OF THE DRAWINGS

[0025] Figure 1 is the X-ray powder diffraction pattern of the low-purity kaolin G0 used as the raw material in Example 1;

[0026] Figure 2 The RTC of the low-purity kaolin G0, G0-50°-1M, G0-50°-2M, G0-50°-3M, G0-50°-4M, and G0-50°-5M of Example 1 is (xyz) and specific surface area S BET picture;

[0027] Figure 3 It is a comparison chart of carbon dioxide adsorption of low-purity kaolin G0 and G0-50°-1M, G0-50°-2M, G0-50°-3M, G0-50°-4M, and G0-50°-5M in Example 1;

[0028] Figure 4 The main crystal plane (001) and main end planes (010), (-110), and (-1-11) of the kaolin of Example 1;

[0029] Figure 5 is the adsorption energy of CO2 by the main crystal plane (001) and the main end planes (010), (-110), and (-1-11) of the kaolin in Example 1;

[0030] Figure 6is the Gibbs free energy of the Cl reaction between the main crystal face (001) and the main end face (010) of the kaolin in Example 1 and HCl;

[0031] Figure 7 The RTC of low-purity kaolin G0 and G0-90°-5M as raw materials in Example 2 (xyz) and specific surface area S BET picture;

[0032] Figure 8 This is a comparison chart of the carbon dioxide adsorption of the low-purity kaolin G0 and G0-90°-5M, which are the raw materials of Example 2;

[0033] Fig. 9 The X-ray powder diffraction pattern of the high-purity kaolin G1 used as the raw material in Examples 2 and 3;

[0034] Fig.10 The RTC of the raw materials high-purity kaolin G1, G1-90°-1M, G1-90°-2M, G1-90°-3M, G1-90°-4M and G1-90°-5M in Example 3 is as follows: (xyz) and BET graph;

[0035] Fig.11 This is a comparison chart of the carbon dioxide adsorption of the raw materials high-purity kaolin G1 and G1-90°-5M according to Example 3;

[0036] Fig.12 According to the RTC of high purity kaolin G1 and G1-50°-1M as raw materials in Example 4 (xyz) and BET graph;

[0037] Fig.13 This is a comparison chart of the carbon dioxide adsorption of high-purity kaolin G1 and G1-50°-1M as raw materials in Example 4;

[0038] Fig.14 The RTC of G1-90°-5M and G1-90°-5M-100° in this embodiment 5 is (xyz) and BET graph;

[0039] Fig.15 This is a comparison chart of the carbon dioxide adsorption of the raw materials high-purity kaolin G1-90°-5M and G1-90°-5M-100° of Example 5;

[0040] Fig.16 The RTC of G1-90°-5M and G1-90°-5M-200° in this embodiment 6 is (xyz) and BET graph;

[0041] Fig.17This is a comparison chart of the carbon dioxide adsorption of the raw materials high-purity kaolin G1-90°-5M and G1-90°-5M-200° of Example 6;

[0042] Fig.18 The RTC of G0 and G0-100° in this comparative example (xyz) and BET graph;

[0043] Fig.19 Comparison chart of carbon dioxide adsorption of high-purity kaolin G0 and G0-100°, the raw materials of this comparative example. DETAILED DESCRIPTION

[0044] The following are specific embodiments of the present invention and the accompanying drawings to further describe the technical solution of the present invention, but the present invention is not limited to these embodiments.

[0045] Embodiment 1:

[0046] In this embodiment, kaolin G0-50°-1M, G0-50°-2M, G0-50°-3M, G0-50°-4M, and G0-50°-5M are prepared.

[0047] Take 1g of kaolin G0 with a purity of 85.9%, add it to 40mL of 1-5M hydrochloric acid, stir it in a water bath at 50℃, stir it at a speed of 200r / min, and react it for 12h. After the reaction, centrifuge it at a speed of 4000r / min, wash it with deionized water until the pH is neutral, put it in an oven at 80℃ to dry it for 12h, cool it to room temperature, take it out and grind it thoroughly to obtain powdered samples G0-50°-1M, G0-50°-2M, G0-50°-3M, G0-50°-4M, G0-50°-5M. Use thermogravimetric equipment to detect its CO2 adsorption capacity.

[0048] The relative texture coefficients (RTCs) of kaolin crystal planes, where I (hkl) is the strength of the textured sample, I 0(hkl) is the strength of the standard oriented sample. RTC (xyz) Represents the sum of the RTCs of the main end faces. The larger the value, the more exposed the end faces are. (020), (-110), (-1-11), (-201), (-131) and (-202) are the main end faces.

[0049] RTC (hkl) =(I (hkl) / I 0(hkl) ) / (∑[(I (hkl) / I 0(hkl) ))*100

[0050] See attached Figure 1, is the X-ray powder diffraction spectrum of the low-purity kaolin G0 as the raw material according to the technical solution of this embodiment. The result shows a high-intensity potassium feldspar miscellaneous peak (Microcline), which is indeed low-purity kaolin.

[0051] See attached Figure 2 , is the RTC of low-purity kaolin G0, G0-50°-1M, G0-50°-2M, G0-50°-3M, G0-50°-4M, G0-50°-5M as raw materials according to the technical scheme of this embodiment (xyz) and specific surface area S BET Figure; It can be seen that the RTC of kaolin G0 (xyz) is 55.31, BET is 11.99m 2 / g, and the prepared G0-50°-1M RTC (xyz) Increased to 64.81, BET had a slight fluctuation of 11.46m 2 / g. According to RTC (xyz) The size order is: G0-50°-1M>G0-50°-3M>G0-50°-2M>G0-50°-4M>G0-50°-5M>G0, according to S BET The size order is: G0-50°-5M>G0-50°-4M>G0-50°-3M>G0>G0-50°-1M>G0-50°-2M.

[0052] See attached Figure 3 , is a comparison chart of the carbon dioxide adsorption of low-purity kaolin G0 and G0-50°-1M, G0-50°-2M, G0-50°-3M, G0-50°-4M, and G0-50°-5M according to the technical scheme of this embodiment, which shows that the carbon dioxide adsorption of kaolin G0 increases from 12.32 mg CO2 / g increases to a maximum of 26.96mg at G0-50°-1M CO2 / g. The carbon dioxide adsorption capacity of G0-50°-2M, G0-50°-3M, G0-50°-4M and G0-50°-5M is 16.59mg CO2 / g, 16.98mg CO2 / g, 12.73mg CO2 / g, 14.17mg CO2 / g. These carbon dioxide adsorption capacities are somewhat improved compared to G0. The carbon dioxide adsorption capacity of materials with increased relative texture coefficients (RTCs) is significantly increased.

[0053] See attached Figure 4, which is a diagram of the main crystal plane (001) and main end planes (010), (-110), and (-1-11) of kaolin according to the technical solution of this embodiment. It is clearly shown that there are more -OH on the main end planes, which can allow more chemical adsorption of -OH+CO2→-HCO3 to occur, which is the basis for judging the relative texture coefficients (RTCs).

[0054] See attached Figure 5 , is the adsorption energy of CO2 on the main crystal face (001) and main end faces (010), (-110), and (-1-11) of kaolin according to the technical solution of this embodiment. The more negative the adsorption energy, the more favorable the crystal face is for adsorbing CO2. The main end faces are obviously easier to adsorb CO2. The DFT calculation results are consistent with the presence of more -OH on the end faces and the experimental results.

[0055] See attached Figure 6 , is the Gibbs free energy of the Cl-reaction between the main crystal face (001) and the main end face (010) of kaolin and HCl according to the technical solution of this embodiment. A negative Gibbs free energy represents that the reaction can proceed spontaneously, and a positive Gibbs free energy represents that the reaction may not proceed spontaneously. Therefore, the main crystal face (001) mainly reacts with HCl, while the end face is more inert. Therefore, acidification can expose the end face of low-purity kaolin. The DFT calculation results are consistent with the experimental results.

[0056] The low-purity kaolin carbon dioxide adsorbents provided by the present invention are G0-50°-1M, G0-50°-2M, G0-50°-3M, G0-50°-4M, and G0-50°-5M. Among them, G0-50°-1M has a larger sum of the relative texture coefficients of the main end faces, which means that the main end faces are more exposed, and therefore has excellent carbon dioxide adsorption performance.

[0057] Embodiment 2:

[0058] This example prepares kaolin G0-90°-5M.

[0059] Take 1g of kaolin G0 with a purity of 85.9%, add it to 40mL of 5M hydrochloric acid, stir it in a water bath at 90℃, stir it at a speed of 200r / min, and react it for 12h. After the reaction, centrifuge it at a speed of 4000r / min, wash it with deionized water until the pH is neutral, put it in an oven at 80℃ to dry it for 12h, cool it to room temperature, take it out and grind it thoroughly to obtain a powdered sample G0-90°-5M. The CO2 adsorption capacity is detected by thermogravimetric equipment.

[0060] See attached Figure 7 , is the RTC of low-purity kaolin G0 and G0-90°-5M as raw materials according to the technical scheme of this embodiment (xyz) and specific surface area S BETFigure; It can be seen that the RTC of kaolin G0 (xyz) is 55.31, BET is 11.99m 2 / g, and the prepared G0-90°-5M RTC (xyz) Increased to 58.89, BET had a slight fluctuation to 32.72m 2 / g.

[0061] See attached Figure 8 , which is a comparison chart of the carbon dioxide adsorption of low-purity kaolin G0 and G0-90°-5M as raw materials according to the technical solution of this embodiment, illustrating that the carbon dioxide adsorption of kaolin G0 increases from 12.32 mg CO2 / g increases to a maximum of 15.2mg at G0-90°-5M CO2 / g. The carbon dioxide adsorption capacity of G0-90°-5M is improved compared with that of G0. The increase of relative texture coefficients (RTCs) and specific surface area leads to the increase of carbon dioxide adsorption capacity.

[0062] The low-purity kaolin carbon dioxide adsorbent G0-90°-5M and G0-50°-1M provided by the present invention has a larger sum of relative texture coefficients of the main end faces, which means that the main end faces are more exposed, and has a high specific surface area, and therefore has excellent carbon dioxide adsorption performance.

[0063] Embodiment 3:

[0064] In this embodiment, kaolin G1-90°-1M, G1-90°-2M, G1-90°-3M, G1-90°-4M, and G1-90°-5M are prepared.

[0065] Take 2g of kaolin G1 with a purity of 98%, add it to 80mL of 1-5 M hydrochloric acid, stir it in a water bath at 90℃, stir it at a speed of 300r / min, and react it for 12h. After the reaction, centrifuge it at a speed of 5000r / min, wash it with deionized water until the pH is neutral, put it in an oven at 80℃ to dry it for 12h, cool it to room temperature, take it out and grind it thoroughly to obtain powdered samples G1-90°-1M, G1-90°-2M, G1-90°-3M, G1-90°-4M, G1-90°-5M. Use thermogravimetric equipment to detect its CO2 adsorption capacity.

[0066] The relative texture coefficients (RTCs) of kaolin crystal planes, where I (hkl) is the strength of the textured sample, I 0(hkl) is the strength of the standard oriented sample. RTC (xyz)Represents the sum of the RTCs of the main end faces. The larger the value, the more exposed the end faces are. (020), (-110), (-1-11), (-201), (-131) and (-202) are the main end faces.

[0067] RTC (hkl) =(I (hkl) / I 0(hkl) ) / (∑[(I (hkl) / I 0(hkl) ))*100

[0068] See attached Fig. 9 , is the X-ray powder diffraction spectrum of the raw material high-purity kaolin G1 according to the technical solution of this embodiment. The results show that it contains fewer impurity peaks and is indeed high-purity kaolin.

[0069] See attached Fig.10 , is the RTC of high purity kaolin G1, G1-90°-1M, G1-90°-2M, G1-90°-3M, G1-90°-4M and G1-90°-5M as raw materials according to the technical scheme of this embodiment (xyz) and BET graph; it can be seen that the RTC of kaolin G1 (xyz) is 64.76, BET is 20.22m 2 / g, while the BET of the prepared G1-90°-5M increased to 50.00m 2 / g,RTC (xyz) is 49.26. According to S BET The size order is: G1-90°-5M>G1-90°-4M>G1-90°-3M>G1-90°-2M>G1-90°-1M>G1. According to RTC (xyz) The size order is: G1>G1-90°-3M>G1-90°-4M>G1-90°-2M>G1-90°-5M>G1-90°-1M.

[0070] See attached Fig.11 , which is a comparison chart of the carbon dioxide adsorption of high-purity kaolin G1 and G1-90°-5M as raw materials according to the technical solution of this embodiment, illustrating that the carbon dioxide adsorption of kaolin G1 increases from 10.3 mg CO2 / g increases to a maximum of 18.92mg for G1-90°-5M CO2 / g. With the increase of hydrochloric acid concentration during acid treatment, the specific surface area increases, and the corresponding carbon dioxide adsorption capacity increases.

[0071] The high-purity kaolin provided by the present invention is mainly controlled by the specific surface area, G1-90°-5M, and has a larger BET, which means that its physical adsorption is stronger, and therefore has excellent carbon dioxide adsorption performance.

[0072] Embodiment 4:

[0073] This example prepares kaolin G1-50°-1M.

[0074] Take 2g of kaolin G1 with a purity of 98%, add it to 80mL of 1M hydrochloric acid, stir it in a water bath at 50℃, stir it at a speed of 300r / min, and react it for 12h. After the reaction, centrifuge it at a speed of 5000r / min, wash it with deionized water until the pH is neutral, put it in an oven at 80℃ to dry it for 12h, cool it to room temperature, take it out and grind it thoroughly to obtain a powdered sample G1-50°-1M. Use thermogravimetric equipment to detect its CO2 adsorption capacity.

[0075] See attached Fig. 9 , is the X-ray powder diffraction spectrum of the raw material high-purity kaolin G1 according to the technical solution of this embodiment. The results show that it contains fewer impurity peaks and is indeed high-purity kaolin.

[0076] See attached Fig.12 , which is the RTC of high-purity kaolin G1 and G1-50°-1M as raw materials according to the technical scheme of this embodiment (xyz) and BET graph; it can be seen that the RTC of kaolin G1 (xyz) is 64.76, BET is 20.22m 2 / g, while the BET of the prepared G1-90°-5M increased to 25.66m 2 / g,RTC (xyz) It is 56.32.

[0077] See attached Fig.13 , which is a comparison chart of the carbon dioxide adsorption of high-purity kaolin G1 and G1-50°-1M as raw materials according to the technical solution of this embodiment, illustrating that the carbon dioxide adsorption of kaolin G1 increases from 10.3 mg CO2 / g increases to a maximum of 17.4mg for G1-50°-5M CO2 / g. As the specific surface area increases, the corresponding carbon dioxide adsorption capacity increases.

[0078] The high-purity kaolin provided by the present invention is mainly controlled by the specific surface area, G1-50°-1M, and has a larger BET, which means that its physical adsorption is stronger, and therefore has excellent carbon dioxide adsorption performance.

[0079] Embodiment 5:

[0080] This example prepares kaolin G1-90°-5M-100°.

[0081] Take 2g of kaolin G1 with a purity of 98%, add it to 80mL1 M hydrochloric acid, stir it in a water bath at 90℃, stir it at a speed of 300r / min, and react it for 12h. After the reaction, centrifuge it at a speed of 5000r / min, wash it with deionized water until the pH is neutral, put it in an oven at 80℃ to dry for 12h, cool it to room temperature, take it out and grind it thoroughly to obtain a powdered sample G1-90°-5M. Take 2g of G1-90°-5M, put it in a muffle furnace with a temperature increase of 10℃ / min and keep it at 100℃ for 60min, cool it to room temperature, and take it out. Use thermogravimetric equipment to detect its CO2 adsorption capacity.

[0082] See attached Fig.14 , is the RTC according to the technical solution G1-90°-5M and G1-90°-5M-100° of this embodiment (xyz) and BET graph; it can be seen that the RTC of G1-90°-5M (xyz) is 51.38, BET is 49.95m 2 / g, and the prepared RTC of G1-90°-5M-100° (xyz) Increased to 52.25, BET had a slight fluctuation to 47.20m 2 / g.

[0083] See attached Fig.15 , is a comparison chart of the carbon dioxide adsorption of high-purity kaolin G1-90°-5M and G1-90°-5M-100° as raw materials according to the technical solution of this embodiment, which shows that the carbon dioxide adsorption of kaolin G1-90°-5M increases from 18.92 mg CO2 / g increases to 23.4mg for G1-90°-5M-100° CO2 / g.

[0084] The kaolin carbon dioxide adsorbent G1-90°-5M-100° provided by the present invention has a larger sum of relative texture coefficients of the main end faces, which means that the main end faces are more exposed, and thus has excellent carbon dioxide adsorption performance.

[0085] Embodiment 6:

[0086] This example prepares kaolin G0-90°-5M-200°.

[0087] Take 2g of kaolin G1 with a purity of 98%, add it to 80mL1 M hydrochloric acid, stir it in a water bath at 90℃, stir it at a speed of 300r / min, and react it for 12h. After the reaction, centrifuge it at a speed of 5000r / min, wash it with deionized water until the pH is neutral, put it in an oven at 80℃ to dry for 12h, cool it to room temperature, take it out and grind it thoroughly to get the powdered sample G1-90°-5M. Take 2g of G1-90°-5M, put it in a muffle furnace with a temperature increase of 10℃ / min and keep it at 200℃ for 60min, cool it to room temperature, and take it out. Use thermogravimetric equipment to detect its CO2 adsorption capacity.

[0088] See attached Fig.16 , is the RTC according to the technical solution G1-90°-5M and G1-90°-5M-200° of this embodiment (xyz) and BET graph; it can be seen that the RTC of G1-90°-5M (xyz) The RTC of the prepared G1-90°-5M-200° is 51.38. (xyz) Increased to 53.68. However, high temperature calcination caused a slight decrease in BET.

[0089] See attached Fig.17 , which is a comparison chart of the carbon dioxide adsorption of high-purity kaolin G1-90°-5M and G1-90°-5M-200° as raw materials according to the technical scheme of this embodiment, illustrating that the carbon dioxide adsorption of kaolin G1-90°-5M increases from 18.92 mg CO2 / g increases to 23.3mg for G1-90°-5M-200° CO2 / g.

[0090] The kaolin carbon dioxide adsorbent G1-90°-5M-200° provided by the present invention has a larger sum of relative texture coefficients of the main end faces, which means that the main end faces are more exposed, and thus has excellent carbon dioxide adsorption performance.

[0091] Comparative Example 1:

[0092] This example prepares kaolin G0-100°.

[0093] 2 g of kaolin G0 with a purity of 85.9% was taken and placed in a muffle furnace with a temperature increase of 10°C / min and kept at 100°C for 60 min, cooled to room temperature, and taken out to obtain G0-100°. The CO2 adsorption capacity was tested using a thermogravimetric device.

[0094] See attached Fig.18 , is the RTC of the comparative example technical solution G0 and G0-100° (xyz) and BET graph; we can see that the RTC of G0 (xyz)is 55.31, BET is 11.99m 2 / g, and the prepared RTC of G0-100° (xyz) Reduced to 45.43, BET reduced to 10.50m 2 / g.

[0095] See attached Fig.19 , which is a comparison chart of the carbon dioxide adsorption of high-purity kaolin G0 and G0-100° as raw materials according to the technical scheme of this comparative example, illustrating that the carbon dioxide adsorption of kaolin G0 increases from 12.32 mg CO2 / g is reduced to 10.39mg at G0-100° CO2 / g.

[0096] The comparative kaolin carbon dioxide adsorbent G0-100° provided by the present invention has a smaller sum of relative texture coefficients of the main end faces after heat treatment at 100°, which means that the less the main end faces are exposed, the smaller the BET becomes, and the heat treatment leads to a decrease in pores and a decrease in physical adsorption capacity. Therefore, its carbon dioxide adsorption performance is reduced.

[0097] For matters not mentioned above, the prior art applies.

[0098] Although some specific embodiments of the present invention have been described in detail through examples, those skilled in the art should understand that the above examples are for illustration only and are not intended to limit the scope of the present invention. Those skilled in the art to which the present invention belongs may make various modifications or supplements to the specific embodiments described or replace them in a similar manner, but they will not deviate from the direction of the present invention or exceed the scope defined by the attached claims. Those skilled in the art should understand that any modifications, equivalent substitutions, improvements, etc. made to the above embodiments based on the technical essence of the present invention should be included in the protection scope of the present invention.

Claims

1. An application of a kaolin-based carbon dioxide adsorbent, characterized in that: The kaolin-based carbon dioxide adsorbent is used to adsorb carbon dioxide. The preparation method of the kaolin-based carbon dioxide adsorbent is as follows: kaolin with a purity of 96-99% and hydrochloric acid with a concentration of 1-5M are stirred in a water bath at 50-90°C, followed by centrifugal separation, washing with ionized water until the pH is neutral, drying, cooling, grinding, heat-activating treatment, and then cooling to room temperature to obtain a sample, namely the kaolin-based carbon dioxide adsorbent; the specific surface area of ​​the kaolin-based carbon dioxide adsorbent is greater than 20 m 2 / g; Stirring speed 100-300 r / min, reaction 6-12 h; Thermal activation treatment was carried out in a muffle furnace with a temperature increase of 5-10 °C / min and maintained at 100-400 °C for 60 min; The sum of the relative texture coefficients (RTCs) of the end surfaces (020), (-110), (-1-11), (-201), (-131) and (-202) of the kaolin-based carbon dioxide adsorbent is greater than 51; , Among them I (hkl) is the strength of the textured sample, I 0(hkl) is the strength of the standard oriented sample.

2. The use according to claim 1, characterized in that: The reaction temperature was 90°C with stirring in a water bath.

3. The use according to claim 1, characterized in that: Dry in an oven at 60-80℃ for 6-12 h.

Citation Information

Patent Citations

  • Method for preparing livestock wastewater adsorbent from acid modified kaolin

    CN106492746A